Clues to the Blues: Predictors of Self-Reported Mental and Emotional Health Among Older African American Men - Mitchell, Jamie A. (Am J Mens Health, 2015)
The mental health needs of aging African American men have been overlooked and few studies have distinguished between more severe clinically diagnosable mental health challenges and less severe emotional states for this population. African American men may not identify with or internalize the terminology of “depression” despite exhibiting the symptom criteria. This exploratory cross-sectional study examined correlates of “downheartedness” as an alternative indicator of emotional health. The authors examined the self-reported responses of 1,666 older African American men on a baseline questionnaire from a larger longitudinal study. Demographic, physical, mental and emotional health, and health system factors were examined as possible correlates of downheartedness. The mean age of participants was 73.6 years and 74.8% of men described themselves as “downhearted and blue” most or all of the time while only 18.5% of them reported feeling moderate to severe anxiety or depression. When other factors were controlled, mobility problems (odds ratio [OR] = 2.36), problems getting health care (OR = 2.69), having a doctor who never listens (OR = 2.18), physical or mental problems that interfere with social activities (OR = 1.34), accomplishing less due to physical health (OR = 1.35), and accomplishing less due to mental/emotional health (OR = 1.57) were all associated with greater odds of being downhearted. The current findings indicate that this sample more closely identified with language accurately describing their emotional health state (i.e., downhearted) and not with clinical mental health terminology (i.e., depression) that may be culturally stigmatized.